A new species of Homonota (Reptilia: Squamata: Gekkota: Phyllodactylidae) from the Ventania mountain range, Southeastern Pampas, Buenos Aires Province, Argentina - Avila, Luciano Javier; Perez, Cristian Hernan Fulvio; Minoli, Ignacio; Morando, Mariana (Zootaxa, 2012)
A new species of lizard genus Homonota from southern Buenos Aires Province, Argentina is described. Homonota wil-liamsii sp. nov. was previously considered as part of the H. darwinii species, but differs by a combination of charactersfrom the nominal species and from other species of the genus. Its geographic distribution is restricted to an isolated mountain system not connected with other habitats suitable for Homonota darwinii